From fast to slow risks: shifting vulnerabilities of flood-related migration in Lodwar, Kenya - Korzenevica-Proud, N; Ng'asike, PO; Ngikadelio, M; Lokomwa, D; Ewoton, P; Dyer, E (Elsevier, 2024)
Migration triggered by climate variability or climate change is often a problematic yet nearly unavoidable adaptation measure, particularly due to the increasing severity of natural hazards. How relocation is negotiated, and risks are evaluated at different scales are still poorly understood. We discuss the temporality and complexity of risks, that are experienced and approached through socio-spatial differences of intersectional embodiment (Sultana, 2020). The study is based on two flood-related qualitative case studies in the small semi-arid and rapidly growing town of Lodwar in the poorest county of Kenya, Turkana. We propose the typology of fast and slow risks to understand the different strategies, negotiations, and priorities of different people involved. Due to political abstraction, three main slow risks were not addressed: concerning land, water, and income. Consequently, vulnerabilities deepened and shifted at different scales: along the axes of gender and able-bodiedness as women and particularly widows, ageing, sick, and single mothers were bearing the main hardship; but also, between communities as hazard risks were deliberately shifted onto a politically less affluent community. We argue that in the process of negotiations, people have been actively advocating for, trying to manage, and rethinking their slow risks. They have often been employing slow responses, particularly in the form of waiting and reimagining.